Peran Kepuasan Kerja Dipengaruhi Digital Leadership dan Motivasi Kerja Terhadap Employee Engagemet: Studi Pada PT. Jasa Raharja Cabang Nusa Tenggara Timur - Theodorus Victor Seran; Mansyur Abdul Hamid; Hyronimus Se (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to find out (1) Whether digital leadership has a direct effect on employee engagement at PT Jasa Raharja East Nusa Tenggara Branch (2) Whether work motivation has a direct effect on employee engagement at PT Jasa Raharja East Nusa Tenggara Branch (3) Whether digital leadership through job satisfaction has an effect on employee engagement at PT Jasa Raharja East Nusa Tenggara Branch (4) Whether Job Motivation through job satisfaction affecting employee engagement at PT Jasa Raharja East Nusa Tenggara Branch. This research includes causality research using a quantitative approach. The sample in this study is 38 employees of PT Jasa Raharja East Nusa Tenggara Branch. Data was collected with questionnaires that had been tested for validity and reliability. Path Analysis was used to test the hypothesis of this research. The results of this study show that, (1) There is a direct and significant influence of digital leadership Employee Engagement on employee engagement of PT Jasa Raharja East Nusa Tenggara Branch, with a standardized coefficient beta value of (β) 0.837 (2) There is a direct and significant influence of work motivation on employee engagement of PT Jasa Raharja East Nusa Tenggara Branch, with a standardized coefficient beta value of (β) 0.894. (3) There is an indirect and significant influence of digital leadership through job satisfaction on employee engagement at PT Jasa Raharja East Nusa Tenggara Branch directly and significantly Job Satisfaction on teachers of SMKN 1 Ende, with a standardized coefficient beta value of (β) 0.604. (4) There is an indirect and significant influence of work motivation through job satisfaction on employee engagement at PT Jasa Raharja Nusa Tenggara Branch, with a standardized coefficient beta value of (β) 0.684.